2019
DOI: 10.1210/jc.2019-00365
|View full text |Cite
|
Sign up to set email alerts
|

The Steroid Profile of Adrenal Incidentalomas: Subtyping Subjects With High Cardiovascular Risk

Abstract: Context Steroid profiling by mass spectrometry has shown implications for diagnosis and subtyping of adrenal tumors. Objectives To investigate steroid profiles and their cardiovascular correlates in a large cohort of patients with nonsecreting (NS) adrenal incidentalomas and autonomous cortisol secretion (ACS). Design Cohort study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 28 publications
1
19
0
4
Order By: Relevance
“…We have identified six studies that have reported the prevalence of smoking in patients with or without ACS/pACS (10,11,12,13,14,15). Only two of these reported an increased prevalence of smoking among patients with ACS/pACS (14,15). However, all these studies were considerably smaller than ours and differences in smoking habits between groups were not adjusted for plausible confounding factors such as gender and age.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…We have identified six studies that have reported the prevalence of smoking in patients with or without ACS/pACS (10,11,12,13,14,15). Only two of these reported an increased prevalence of smoking among patients with ACS/pACS (14,15). However, all these studies were considerably smaller than ours and differences in smoking habits between groups were not adjusted for plausible confounding factors such as gender and age.…”
Section: Discussionmentioning
confidence: 59%
“…Smoking habits were also linked to cortisol ONDST with smokers having cortisol ONDST ≥50 nmol/L more often, both among patients with unilateral and bilateral adrenal incidentalomas. We have identified six studies that have reported the prevalence of smoking in patients with or without ACS/pACS (10,11,12,13,14,15). Only two of these reported an increased prevalence of smoking among patients with ACS/pACS (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Although patients with MACS-CPA could present comorbidities associated to mild cortisol hypersecretion, such as risk of cardiovascular events, hypertension, dyslipidemia, diabetes mellitus type 2, obesity, osteoporosis (13,(15)(16)(17)(18)(19), the long-term data did not provide evidence for an evolution from MACS-CPA to overt CS (32). Additionally, recent analysis by liquid chromatography tandem mass spectrometry in patients with adrenal incidentalomas showed that the steroid profiling of subjects with EIA showed some similarities with those having MACS-CPA (33,34).…”
Section: Discussionmentioning
confidence: 96%
“…However, again in these patients, measuring cortisol and its metabolites by immunoassay could be more representative of real glucocorticoid (GC) secretion and, possibly more predictive of clinical outcomes, than measuring only pure cortisol levels by LC-MS/MS. Therefore, the use of LC-MS/MS measurement of a comprehensive steroid profile, rather than cortisol alone, could be proposed for the detection of subtle excess GC in patients with incidentally discovered adrenal masses (42,43). In addition, 11-deoxycortisol in serum or urine could become a sensitive marker of residual adrenal function in the future.…”
Section: What and How To Measurementioning
confidence: 99%